PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATERI MENULIS TEKS EKSPOSISI DENGAN TEKNIK COPY THE MASTER SISWA KELAS X SMK KARTIKA 1-2 PADANG - Ningsih, Ade Yulia; R., Syahrul; Noveria, Ena (Universitas Negeri Padang, 2018)
ABSTRACT This study aims to (1) describe the process of developing LKS with copy the master technique for learning to write valid exposition text, (2) practicalÂ and (3) effective. The development mode used is 4-D model consisting of 4 stages, namely define, design, development . This development process produces products in the form of LKS with copy the master technique for expository, valid, and effective expository writing material.The results of this study indicate that the resulting LKS categorized as valid, effective and practical. It is seen based on the value of validity, practicality and effectiveness of LKS. The overall LKS validity score is 77.15%, the average of practicality by teachers is 85% and the student is 83.33%) and effective.Based on the calculation with Likert formula obtained 85.25% results so that the use of LKS model with copy the master technique on writing material exposition effectively.Â Kata kunci: pengembangan , LKS, menulis teks eksposisi, teknik copy the master, validitas, efektivitas, praktikalitas